Atmospheric [Delta] 14CO2 trend in Western European background air from 2000 to 2012 - Levin, Ingeborg; Kromer, Bernd; Hammer, Samuel (Tellus. Series B, Chemical and physical meteorology, 2013)
Long-term measurements of atmospheric Δ14CO2 from two monitoring stations, one in the European Alps (Jungfraujoch, Switzerland) and the other in the Black Forest (Schauinsland, Germany), are presented. Both records show a steady decrease, changing from about 6‰ per year at the beginning of the century to only 3‰ per year on average in the last 4 yr. A significant seasonal variation of Δ14CO2 is observed at both sites with maxima during late summer and minima in late winter/early spring. While the Δ14C maxima are similar at Jungfraujoch and Schauinsland, the minima at Schauinsland are lower by up to 10‰, due to a larger influence from 14C-free fossil fuel CO2 emissions in the footprint of the Schauinsland station in winter. Summer mean Δ14C values at Schauinsland are considered best suited as input for studies of biospheric carbon cycling in mid-northern latitudes or for dating of organic material of the last half century.